2011
DOI: 10.1510/icvts.2010.256784
|View full text |Cite
|
Sign up to set email alerts
|

Post-implantation syndrome following endovascular abdominal aortic aneurysm repair: preliminary data

Abstract: PIS is a relatively common complication of EVAR used to treat AAAs and it is associated with features of a systemic inflammatory response and prolongation of hospitalization. Further studies are necessary towards understanding the underlying pathophysiology and evaluating effective preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 17 publications
2
91
3
1
Order By: Relevance
“…23 A significant decrease in platelet count, an indirect index of platelet activation and consumption, has been observed postoperatively in a substantial proportion of EVAR patients. 3,9 The amount of mural thrombus has also been proposed to incur a role in the inflammatory response, as PIS initially was linked with the release of inflammatory mediators from the aneurysm thrombus. 15,16 Kakisis et al 24 recently evaluated nearly 85 patients after EVAR and reported an association between new onset thrombus and PIS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…23 A significant decrease in platelet count, an indirect index of platelet activation and consumption, has been observed postoperatively in a substantial proportion of EVAR patients. 3,9 The amount of mural thrombus has also been proposed to incur a role in the inflammatory response, as PIS initially was linked with the release of inflammatory mediators from the aneurysm thrombus. 15,16 Kakisis et al 24 recently evaluated nearly 85 patients after EVAR and reported an association between new onset thrombus and PIS.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed process has been previously reported. 3 In brief, serum and standard samples were incubated into the micro wells of an enzyme linked immunosorbent assay (ELISA) plate, coated with a mouse monoclonal antibody against the corresponding human molecule. During the incubation a bound complex of antigeneantibody was formed.…”
Section: Blood Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…EVAR may elicit a postoperative systemic inflammatory response, referred to as post-implantation syndrome (PIS) featuring pyrexia, negative blood culture results, leucocytosis, increased C-reactive protein and/or coagulation disturbances [28]. The reported incidence of PIS after EVAR varies widely between 14% and 60% [28], and both underestimation and lack of explicit criteria for this syndrome may account for this large variation [29]. Plasma levels of IL-6 have been shown to increase already on the first postoperative day, culminate at 24 h, and remain increased for at least 6 days [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%